A2 5 Localised Entirely Within Your Kitchen - Steele, Ethan; Hamade, Ceres; Cooper, Sam (Physics Special Topics, 2023)
In the Simpsons segment known as ``Skinner And The Superintendent", Skinner claims the aurora borealis is localised entirely within his kitchen, which shocks the Superintendent. In this paper we found the magnetic field strength required for a magnet, placed in the middle of Skinner's kitchen, to produce an aurora with the radius of said kitchen through collisional ionisation. We find this to be 5.65 × 10^16 Tesla, a billion times greater then the magnetic field produced by the strongest neutron stars [3].